Two lectotypifications of names of Peruvian endemic species of the genus Tarasa Phil. (Malvaceae) - Mazzei, Piero (2025)
Tarasa is a genus endemic to the Americas that is represented in Peru by 14 species. In the context of the taxonomic treatment of this genus for the Peruvian flora, two names of species that need to be typified to stabilize their nomenclature were identified. For the nomenclatural treatment, the protologues are analyzed and the type material is studied in physical or through online images. Lectotypifying is carried out in accordance with the indications of the current International Code of Nomenclature for Algae, Fungi and Plants. Lectotypes are designated for two names of Tarasa species endemic to Peru.